Analysis of IKEA's Internationalization Strategy - Saud Alenezi; Nouf Al Mutairi; Saif Alenezi; Sarah Maresa Münzer (AIBPM Publisher, 2019)
IKEA is one of the most recognizable home furniture brands worldwide. Its concept focuses on combining high functionality with quality and design in its products, while keeping prices as low as possible, especially by keeping the assembly of the furniture directly at the customer. Its stores usually also include a kid’s area and a restaurant, where you can buy besides others their in-house brands of food and snacks. It’s goal from the beginning was to provide furniture that makes everyday life easier and is available to everyone and not only a few people, all of this while keeping sustainability in mind. IKEA is a very family-oriented company, with the belief that children are the most important people and the home is the most important place. It was founded 1945 by Ingvar Kamprad in Sweden, who handed the Ownership of the company over in 1982, to ensure the companies independence even after he wouldn’t be able to take care of it anymore. (IKEA Foundation, 2019) The IKEA Group works with a franchise System and multiple different companies, all under the IKEA Brand. (Inter IKEA Systems, 2017) The company has grown significantly over the past decades, with revenues reaching a billion dollars recently. IKEA has over three hundred stores in 55 different countries, and become the third largest consumer of wood worldwide. (Jamila Sidhpurwala, 2018) While expanding at a very fast rate and with huge success in the european market, it faced many challenges, some of them within their company structure and others while trying to enter markets outside of Europe. One of the major and critical problems IKEA faced in recent years is uncontrolled child labour in countries that supply woven products like carpets to the company. Child labour in countries such as India and Pakistan is a common phenomenon and the company lacks effective ways to control its suppliers in these countries. Child labour is often accepted in societies with high poverty rates and parents are having a hard time to support the family on their own. Since Institutions are often weak in those areas too, the company cannot rely on local authorities for assistance. So far, IKEA’s attempts to control this issue have been unsuccessful. IKEA can try to limit or prevent the use of child labour by strengthening and working to amend its agreements with suppliers and put strikt contracts in place that prohibit the exploitation of children and their families. Another huge problem they faced while expanding their markets was the understanding of different cultures and needs. Culture varies from society to another, so they have to adjust their product range and service according to the needs of the customers in each country. (Hultman et al., 2012) In some cases, the company wasn’t able to adjust to the market the way they needed to. One of the most prominent examples for that was the first time they entered the Japanese market in 1974. Because they misunderstood their audience regarding quality as well as service and product requirements among other things, they even closed down their store completely after a couple years. They came back to Japan in 2006, after they adjusted their strategy and adapting their products to the living conditions in the country. (LA Times, 2006) The purpose of this paper is to analyze the challenges IKEA has faced in the past regarding their international expansion, showcase which solutions the company has found so far.